2018
DOI: 10.1155/2018/3817397
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Influences of Drilling Arrangements on the Mechanical Behavior and Energy Evolution of Coal Models

Abstract: Destress drilling method is one of the commonly used methods for mitigating rock bursts, especially in coal mining. To better understand the influences of drilling arrangements on the destress effect is beneficial for rock burst mitigation. This study first introduced the rock burst mitigation mechanism of the destress drilling method and then numerically investigated the influences of drilling arrangements on the mechanical properties of coal models through uniaxial compression tests. Based on the test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Due to the large differences in the impact hazards of normal faults and reverse faults, even if the burial depth is the same, they still show different characteristics 42 , which leads to the difference in the size of the fault coal pillar and the pressure relief program of the drilling holes 43 , 44 . This paper mainly focuses on the impact hazard of the 3301 working face under the influence of the mining zone and the lower plate of the normal fault.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large differences in the impact hazards of normal faults and reverse faults, even if the burial depth is the same, they still show different characteristics 42 , which leads to the difference in the size of the fault coal pillar and the pressure relief program of the drilling holes 43 , 44 . This paper mainly focuses on the impact hazard of the 3301 working face under the influence of the mining zone and the lower plate of the normal fault.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the roof fracture-type rock burst has the characteristics of high occurrence frequency, large impact strength and massive energy release, which seriously threatens the production safety of coal seam (Tan et al 2021;Guo et al 2019a). Many studies (Marcak 2012;Zhao et al 2018c) have shown that thick and hard roof is a typical geological condition that induces roof fracture-type rock burst, and the large amount of energy released by fracture under the action of bending load is the root cause of roof fracture-type rock burst. Therefore, the mechanical properties and energy release laws of rock beams with different lithologies and thicknesses under bending loads are issues of great concern in the field of coal mining engineering.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the monitoring and early warning methods for rock burst are mainly divided into two categories: traditional rock mechanics methods (e.g., drilling cutting method, coal and rock mass stress measurement, and core discing method) [16][17][18][19][20][21] and geophysical methods (e.g., electromagnetic radiation (EMR), microseismic (MS), and acoustic emissions (AE)) [11,[22][23][24][25][26][27]. In recent years, geophysics method has been widely used in underground because of its advantages of noncontact, data continuity, and automatic monitoring.…”
Section: Introductionmentioning
confidence: 99%